Processo administrativo sancionador na UTFPR: diagnóstico e elementos para uma proposta de dosimetria - Prado, Jefferson da Silva (2018)
The participation of companies in bids and contracts of the federal government does not always end in a positive way, as the committing of some irregularity can bring penalties ranging from a simple warning, to the impossibility of returning to work with a public institution, in addition to a fine. Through the Judgment of the Court of Auditors of the Union (CAU) and the publication of guidelines for the process of sanctioning companies, it was clear that managers can not refrain from applying these sanctions. A descriptive research was carried out using several forms of data collection - bibliographic and documentary research, interview, participant observation, questionnaire - with the objective of proposing a dosimetry for sanctioning administrative procedures (SAP), arising from any irregularities practiced during the bidding process of Electronic Auction at UTFPR. The research clarified the reasons for this type of SAP starting only in 2015, presented a diagnosis of the situation in the various campuses, punctuated the topics most treated in research and manuals on the sanction process, analyzed documents used as guidelines in several institutions, typified the main irregularities and suggested dosimetry, aggravating and attenuating factors for the moment of choosing the sanction, in order to ensure compliance with de principle of reasonableness and proportionality